Italy's Jews from emancipation to fascism - Klein, Shira (Cambridge University Press, 2018)
How did Italy treat Jews during World War II? Historians have shown beyond doubt that many Italians were complicit in the Holocaust, yet Italy is still known as the Axis state that helped Jews. Shira Klein uncovers how Italian Jews, though victims of Italian persecution, promoted the view that Fascist Italy was categorically good to them. She shows how the Jews' experience in the decades before World War II - during which they became fervent Italian patriots while maintaining their distinctive Jewish culture - led them later to bolster the myth of Italy's wartime innocence in the Fascist racial campaign. Italy's Jews experienced a century of dramatic changes, from emancipation in 1848, to the 1938 Racial Laws, wartime refuge in America and Palestine, and the rehabilitation of Holocaust survivors. This cultural and social history draws on a wealth of unexplored sources, including original interviews and unpublished memoirs